Environmental Consequences Of Urban Expansion: Case Study Of Environmental Licensing Processes In The Municipality Of Governador Valadares - Sara Carolina Soares Guerra Fardin; Talita Jardim do Nascimento; Henrique Delboni Fardin (Geography, Environment, Sustainability, 2021)
Urban growth is often accompanied by significant environmental changes, which include modification of the natural landscape and the problems related to it, such as real estate speculation, marginalization of the population, landslide risks, flooding, as well as pressure on environmentally protected areas. Therefore, it is necessary to understand how will new urban development affect the already modified space without generating further environmental problems. The research aimed to analyse five projects of allotments in Governador Valadares/Brazil between 2015 and 2017. Besides the information on the projects themselves, geographic information systems (GIS) were used along with laws and bibliography. The biggest obstacle observed was the lack of standardization in the process required by the City Hall, which culminated in projects with different characteristics, including those that did not present important analyzes, such as the Civil Construction Waste Management Plan. It is necessary to move forward in discussions related to urban environmental sustainability, standardizing the possible actions, not only in the municipality of Governador Valadares.